An Efficient and Secure Steganography Technique Using Edge Adaptive Technique - Singla, Neha; Saini, Khushil Kumar (International Journal of Computer Sciences and Engineering, 2025)
This paper presents an edge based embedding technique to achieve undetectability in steganography with minimal amount of distortion. In this method, desired information is embedded in the edges, as the edges are least susceptible to Human Visual System (HVS) and therefore, remains concealed. Further, the proposed technique uses Majority Parity Check to improve the PSNR of image. The prominent issue with steganography is the amount of distortion caused due to embedding. The proposed technique offers the flexibility of attaining high security with minimal distortion. Experimental results show that the technique provides reduction in the distortion by 20% in comparison to other well-known techniques available in literature.